2010
DOI: 10.1016/j.placenta.2010.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor (VEGF) and VEGF-receptor expression in placenta of hyperglycemic pregnant women

Abstract: Hyperglycemia occurs in a variety of conditions such as overt diabetes, gestational diabetes and mild hyperglycemia, all of which are generally defined based on the oral glucose tolerance test and glucose profiles. Whereas diabetes has received considerable attention in recent decades, few studies have examined the mechanisms of mild hyperglycemia and its associated disturbances. Mild gestational hyperglycemia is associated with macrosomia and a high risk of perinatal mortality. Morphologically, the placenta o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
44
2
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 36 publications
5
44
2
5
Order By: Relevance
“…Thus, the results of immunohistochemical study of normal placenta were generally consistent with published data on the distribution of VEGF and its receptors [1,3,12]. We found predominance of nonbranching angiogenesis in the placentas from obese women.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, the results of immunohistochemical study of normal placenta were generally consistent with published data on the distribution of VEGF and its receptors [1,3,12]. We found predominance of nonbranching angiogenesis in the placentas from obese women.…”
Section: Resultssupporting
confidence: 91%
“…Vascular endothelial growth factor (VEGF) plays the key role in placental angiogenesis by regulating the development of new blood vessels through interaction with the corresponding tyrosine kinase receptors [2,12].…”
mentioning
confidence: 99%
“…Previous findings by our group have shown alterations in vascular proliferation, such as biomarkers (VEGF and receptors) and apoptosis (caspase 3), in placentas from pregnancies complicated by maternal hyperglycemia [15][16][17][18]. Some of these findings confirmed that the maternal glycemic mean (GM), in the threshold of 100 to 120 mg/dL, would be a determining factor for alterations in angiogenesis and placental vascularization with repercussions on the nutrition and oxygenation functions of the developing fetus.…”
Section: Introductionmentioning
confidence: 82%
“…The leading role in angiogenesis processes in the placenta is played by vascular endothelial growth factor (VEGF) regulating the development of new blood vessels via interaction with the corresponding tyrosine kinase receptors [7,9].…”
mentioning
confidence: 99%